Hormonal Profile Changes as A predictive Marker for Polycystic Ovary Syndrome and Infertility in Women - Badr Manhy Alkhaleeli, Abdulmutalb (Pure Sciences International Journal of Kerbala, 2024)
Background: This study aims to examine the role of hormones that are important for controlling female reproductive processes: the follicle-stimulating hormone (FSH), Sex binding globulin (SBHG), luteinizing hormone (LH), testosterone (T) and free testosterone (FT) levels as a prognostic marker among polycystic ovary syndrome (PCOS) patients, and their relationship with obesity . Design and Methods: This study included one hundred samples of Iraqi patients aged between (25 and 40) years. A healthy BMI level is around (20-24.9) kg/m2, and around (25-29.9) kg/m2 is overweight. Then, when BMI is more than (30kg / m2), the woman is considered fat. The groups are collected from the Obstetrician and Gynecologist” in Karbala Hospital from December 2023 to March 2024. BMI, waist-to-hip ratio (WHR), LH, FSH, TT, FT, and SHBG levels were evaluated in each subject. Results: A significant increase in LH (P=0.0001), FSH levels (p=0.05), LH/FSH ratio (P=0.0001), TT (p=0.025), and FT (p=0.0001) in PCOS patients compared to the control group. However, the SHBG level (p=0.0001) in PCOS patients compared to the control group was significantly diminished.